Wie der Lehrer, so die Schule - Zu valenzrelevanten Eigenheiten des Unterrichtsgesprächs hinsichtlich einer Kommunikationsbefähigung im Deutschunterricht - ZIMMERMANN, Constanze (Uniwersytet im. Adama Mickiewicza, 1995)
The starting point of the discussion about the school language are the two basic elements of communication - question and answer, whereas the most important is the logical and semantic contents of those two units of every dialogue, and of secondary importance - their realization in the language and the external determinants of the act of communication. The term “valence” is understood here as the valence of every element in relation to the contiguity which examined outside the langue. Having considered its three surfaces of occurrence (as the feature, relation and the potency), one may describe valence as a definite regularity of the verbal behaviour. The paper is summed up with a statement on the role of the teacher, steering and determining the behaviour of the pupil.